육군간부의 건강관리 개선에 관한 연구 : 건강에 대한 지식과 건강 행위를 중심으로 - 박현주 (연세대학교 보건대학원, 1990)
[한글] 이 연구는 장교, 하사관의 건강지식과 관심도 및 건강에 관계된 행위와 건강진단제도에 대한 관심사를 파악하여 군 장병의 건강증진과 질병예방에 대한 기초자료를 제공하기 위한 목적을 가지고 1990년 4월 20일부터 4월 30일 사이에 00개 사단에 근무하는 453명을 대상으로 자기기입식의 구조화된 조사표를 이용 자료를 수집하였다. 이를 분석한 연구 결과는 다음과 같다. 1. 흡연율은 76.8%이었으며 근속년수가 많고, 교육수준이 낮은 경우와 기혼자인 경우에 흡연율이 더 높았다. 2. 흡연시작연령의 평균은 20.6세이었으며, 계급간에 통계학적으로 유의한 차이가 있었고, 흡연시작연령 19세 이하인 군의 일일평균흡연량이 가장 많았다. 3. 음주율은 89.6%이었고, 음주시작연령의 평균은 20.4세, 월평균 음주횟수는 6.2회였다. 4. 응답자의 건강지식수준에 영향을 미치는 변수로 교육연수와 근속년수가 통계학적으로 유의하였으며 교육연수와 근속년수가 많을수록 지식수준은 높았다. 5. 응답자의 건강관심도에 영향을 미치는 변수는 근속연수, 흡연시작연령 그리고 운동시간이 통계학적으로 유의하였으며 근속년수와 운동시간이 많을수록, 흡연시작연령이 늦을수록 건강관심도가 높았다. 6. 응답자의 주당 평균운동시간은 148.5분이었다. 7. 응답자의 계급과 교육수준이 낮을수록 신검만족도가 높았으며, 현행신검제도에서 44.4%가 검사종목의 증가를, 22.3%가 신검횟수의 증가를 요구하였다. 위의 결과로 보아 장병의 건강관리가 효과적으로 정착되기 위해서는 장병에 대한 건강교육과 진료기관등의 수준 향상을 통하여 장병의 건강증진을 위한 노력이 요구되며 이 연구에서 다루지 못한 부분과 제한점을 보완할 수 있는 심층 연구가 필요하다. [영문] This study was designed to measure health knowledge, concerns, behavior, and the effectiveness of health screening program in Korean army. A questionnaire survey was conducted from April 20 to April 30, 1990 and data were collected from 266 army officers and 187 non-commissioned officers in several army divisions. The results were as follows : 1. The overall prevalence of smoking was 76.8%. The longer the respondents served and the less the respondents educated, the higher their smoking prevalences were. The married were higher in smoking prevalence than unmarried. 2. The average starting age of smoking was 20.6 year, and military rank was significantly related with the starting age of smoking. The respondents who started smoking before the age nineteen consumed the highest volume of cigarettes than others. 3. A total of 89.6% of the respondents were drinkers with the average age of starting drinking 20.4 year. Average frequency of drinking was 6.2 times a month. 4. From the multiple regression analysis the longer the respondents educated and the longer they served, the higher health knowledge level they have. 5. The longer the duration of service and the later the smoking starting age and the longer the average duration of physical exercises, the more concerns about their health. 6. The average duration of physical exercise was 148.5 minutes a week. 7. The respondents with lower military ranks and those with lower education level were more satisfied with the health screening program than others. A total of 44.4% of respondents wanted to increase the number of items of the health screening program, and 22.3% wanted to increase the frequency of the screening program. Based on these results, it is concluded that more health education and strengthened medical services are required for the better health care of military servicemen and that further study is needed in this area.
보건학과/석사